Education for the Challenged Children: Trends and Innovation in East Khasi Hills District of Meghalaya - Paul, Dr Sumana (INDIAN EDUCATIONAL REVIEW, 2012)
The whole world is progressing towards globalisation and India is no exception to it. However, we still neglect the core issues of our country; the children with disability and their inclusion in the normal school curriculum. When significant progress has been made in many countries like USA, UK towards the issue concerned, we cannot afford to be left behind. In every democratic society like India, every child has the right to education, the right to receive help in learning, to the limits of the capacity whether it is great or small. All children are given equal opportunity to learn whether they are average, bright, dull, retarded, blind, crippled, etc. Equality of opportunity denotes two things— equality of access to school education and equality of success in school. In every classroom there are some individuals who by virtue of their disabilities require more relevant or appropriate instruction. A domain of education has been constructed to satisfy learning requirements. The foremost goal of special education is finding and capitalising the children’s special abilities. The National Policy on Education 1986 has made a significant contribution towards developing educational opportunity for the disabled children.